2016
DOI: 10.1039/c6sm00140h
|View full text |Cite
|
Sign up to set email alerts
|

Persulfate initiated ultra-low cross-linked poly(N-isopropylacrylamide) microgels possess an unusual inverted cross-linking structure

Abstract: Cross-linking density and distribution are decisive for the mechanical and other properties of stimuli-sensitive poly(N-isopropylacrylamide) microgels. Here we investigate the structure of ultra-low cross-linked microgels by static light scattering and scanning force microscopy, and show that they have an inverted cross-linking structure with respect to conventional microgels, contrary to what has been assumed previously. The conventional microgels have the largest polymer volume fraction in the core from wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
95
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(99 citation statements)
references
References 49 publications
4
95
0
Order By: Relevance
“…[14, 15] For pNIPAM-A (7 mol% BIS), the average Young’s modulus was determined to be 201 ± 10 MPa from sampling 30 individual particles. This result is consistent with a previous nanoindentation result reported by Tagit et al .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[14, 15] For pNIPAM-A (7 mol% BIS), the average Young’s modulus was determined to be 201 ± 10 MPa from sampling 30 individual particles. This result is consistent with a previous nanoindentation result reported by Tagit et al .…”
Section: Resultsmentioning
confidence: 99%
“…for low BIS (mol% < 2.0%) incorporation and guides the interpretation of our nanoindentation results. [15]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PNIPAm microgels are synthesized in the presence of an exogenous cross-linker, such as N,N′-Methylenebis(acrylamide) (BIS); however, recent studies have demonstrated that pNIPAm microgels can be synthesized in the absence of an exogenous crosslinker, resulting in the formation of ultra-low cross-linked (ULC) particles 14 . Microgel mechanics are easily modulated through alterations in the degree of intra-particle crosslinking.…”
Section: Introductionmentioning
confidence: 99%
“…investigated the structure of ULC pNiPAm microgels by static light scattering. [57] Therein, the particles were prepared via non-stirred precipitation polymerization using KPS as initiator. The scattering experiments of these particles suggest an inverted cross-linking structure having the highest polymer density close to the particle surface.…”
Section: Resultsmentioning
confidence: 99%